Aspectos clínico-epidemiológico das mulheres pós abortamento em hospital do interior do Pará - RESENDE, Nicolas (2022)
OBJECTIVE: Studying aspects clinical, epidemiological and reproductive of patients admitted due abortion in provincial hospital of Pará. METHOD: Descriptive study type cross made at the Municipal Tailândia Hospital – PA (MTH), in the period of March 2010 to June 2011, interviewing 117 women after abortion. RESULTS: The age ranged from 13 to 42 years, with average 24 ± 6 years. The singles women (43.5%), elementary school or high school, with average wage family between 2 and 3 minimum wage and catholic religion (58.1%). Multiple pregnancies (69.2%) they hadn’t history of abortion (79.49%). They use contraceptive (76.9%) hormonal contraceptive (42.7%) and stopped using it because they forgot (34.2%). In admission, the diagnosis of the spontaneous abortion is 73.3% and incomplete abortion is 60.7%. Among the reasons induced abortions was the fear (38.7%) and lack of partner support (38.7%). In spontaneous abortions predominate unknown causes (45.3%) and some could be observed with more attention: fall (24.4%) and big emotions (16.3%). Prevailed the absence of signs and symptoms (71.8%). In the induced abortion the most was incomplete abortion (77.4%) occurred more than spontaneous abortion. They know that abortion is a crime (86.3%) and that in cases of sexual abuse (47.9%), the abortion can be made legally (54.7%). CONCLUSION: We can’t put away the possibility sub notification. The research try to alert the government and show the necessity to extend studies about the subject to create more effective measures in prevention, training the professionals to get more humane treatment and to combat physical and mental damage, decreasing the morbidity and mortality, as well as the spending of public service.